Supporting doctors' well‐being and resilience during COVID‐19: A framework for rapid and rigorous intervention development. Issue 1 (20th August 2021) - Gibson Smith, Kathrine; Cunningham, Kathryn B.; Cecil, Joanne E.; Laidlaw, Anita; Cairns, Patrick; Scanlan, Gillian M.; Tooman, Tricia R.; Aitken, Gill; Ferguson, Julie; Gordon, Lisi; Johnston, Peter W.; Pope, Lindsey; et al.
Abstract: This paper aims to outline the development of a theoretically informed and evidence‐based intervention strategy to underpin interventions to support the well‐being of doctors during COVID‐19 and beyond; delineate new ways of working were employed to ensure a rapid and rigorous process of intervention development and present the resulting novel framework for intervention development. The research comprised four workstreams: literature review (WS1), qualitative study (WS2), intervention development and implementation (WS3) and evaluation (WS4). Due to time constraints, we employed a parallel design for WS1–3 with the findings of WS1–2 informing WS3 on a continual basis. WS3 was underpinned by the Behaviour Change Wheel. We recruited expert panels to assist with intervention development. We reflected on decisions taken to facilitate the rapid yet rigorous process of intervention development. The empirical output was a theoretically informed and evidence‐based intervention strategy to underpin interventions to support doctors' well‐being during COVID‐19 and beyond. The methodological output was a novel framework that facilitates rapid and rigorous development of interventions. The intervention strategy provides a foundation for development and evaluation of tailored interventions to support doctors' well‐being. The novel framework provides guidance for the development of interventions where the situation demands a rapid yet rigorous development process.